Augmented Reality Berbasis Android untuk Pengenalan Alat Pernapasan Menggunakan Metode Marker Based Tracking - Pangestu, M. Ridho; Suriati, Suriati (Explorer, 2026)
This study aims to design and implement an Augmented Reality (AR)-based learning application on the Android platform to introduce respiratory organs of living beings, namely lungs, gills, and tracheae, as an effort to improve students’ interest and understanding of biology subjects. The application was developed using the Marker Based Tracking method, chosen for its ability to accurately place virtual objects on predefined markers, resulting in more realistic and interactive 3D visualizations. Development was carried out using Unity 3D and Vuforia SDK as the core AR technology, Blender for creating 3D models, and Canva for designing the interface and markers, with the C# programming language used to manage interaction logic. The application allows users to scan markers to display 3D objects along with descriptive information, providing a more engaging learning experience compared to conventional media. Testing involving 100 students aged 10–14 years showed positive responses, with 93% stating the application is easy to understand, 83% rating the objects as clear, 94% feeling assisted in understanding the material, and 100% reporting greater enthusiasm and ease of learning compared to using books or teachers alone. These results demonstrate that AR can enhance engagement and effectiveness in learning biology. In conclusion, implementing AR in learning media offers an innovative approach that combines interactive visualization with modern technology and has the potential to be further developed by adding more object variations, organ function animations, and multi-platform support.